2012
DOI: 10.1371/journal.pone.0051961
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Approach for the Assessment of Cell Viability and Cell Functionality of Human Fibrochondrocytes for Use in Tissue Engineering

Abstract: Temporo-mandibular joint disc disorders are highly prevalent in adult populations. Autologous chondrocyte implantation is a well-established method for the treatment of several chondral defects. However, very few studies have been carried out using human fibrous chondrocytes from the temporo-mandibular joint (TMJ). One of the main drawbacks associated to chondrocyte cell culture is the possibility that chondrocyte cells kept in culture tend to de-differentiate and to lose cell viability under in in-vitro condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
2
7
0
5
Order By: Relevance
“…In contrast to the immortalized cell clones, primary cells showed little telomerase activity and progressive decrease in expression of the assayed proteins. This effect of passaging on diminution of protein expression in primary cells has been shown in previous studies including those from the human TMJ disc 35,36 . Thus passaging of TMJ fibrochondrocytes retrieved from diseased human TMJs over 9 passages resulted in passage-dependent decrease in cell viability and reduction in expression of genes for several matrix molecules including collagens I, III, IV, V, XV and XVI, the proteoglycans aggrecan, chondroitin sulfate, heparin sulfate, biglycan, decorin, and COMP 36 .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In contrast to the immortalized cell clones, primary cells showed little telomerase activity and progressive decrease in expression of the assayed proteins. This effect of passaging on diminution of protein expression in primary cells has been shown in previous studies including those from the human TMJ disc 35,36 . Thus passaging of TMJ fibrochondrocytes retrieved from diseased human TMJs over 9 passages resulted in passage-dependent decrease in cell viability and reduction in expression of genes for several matrix molecules including collagens I, III, IV, V, XV and XVI, the proteoglycans aggrecan, chondroitin sulfate, heparin sulfate, biglycan, decorin, and COMP 36 .…”
Section: Discussionsupporting
confidence: 79%
“…This effect of passaging on diminution of protein expression in primary cells has been shown in previous studies including those from the human TMJ disc 35,36 . Thus passaging of TMJ fibrochondrocytes retrieved from diseased human TMJs over 9 passages resulted in passage-dependent decrease in cell viability and reduction in expression of genes for several matrix molecules including collagens I, III, IV, V, XV and XVI, the proteoglycans aggrecan, chondroitin sulfate, heparin sulfate, biglycan, decorin, and COMP 36 . Similarly, porcine primary TMJ disc cells undergo significant decreases in gene expression levels of aggrecan, and collagen types I and II by 20%, 23% and 73%, respectively per passage 35 .…”
Section: Discussionsupporting
confidence: 79%
“…MSCs have the ability to differentiate into epithelial cells 93-95 and keratocytes. 96 Our previous work has shown that UMSCs can be used to successfully treat the congenital lysosomal storage disorder mucopolysaccharidosis VII ( MPS VII ).…”
Section: Therapeutic Potential Of Mesenchymal Stem Cellsmentioning
confidence: 99%
“…La eficacia terapéutica de los constructos elaborados por ingeniería tisular depende de factores muy diversos como por ejemplo la naturaleza del biomaterial utilizado y las propiedades reológicas del mismo o del tipo de célula seleccionado. En relación con estas últimas es importante señalar que solo el uso de poblaciones celulares con un grado elevado de viabilidad puede garantizar el éxito y la eficacia terapéutica (5,6,(23)(24)(25).…”
Section: Discussionunclassified
“…La evaluación de los perfiles de viabilidad de las células a utilizar en los constructos generados por ingeniería tisular constituye por tanto uno de los objetivos fundamentales en los protocolos de control de calidad a la hora de autorizar su traslación a la clínica. Como se ha indicado en la introducción los métodos habituales de evaluación de viabilidad basados en la identificación de las alteraciones de la membrana celular y del estado metabólico celular presentan limitaciones importantes que la utilización de la microscopia electrónica analítica por dispersión de Rayos X ha comenzado recientemente a superar (5,6,(23)(24)(25)(26). La evaluación de la viabilidad en los protocolos actualmente existentes se realiza sin embargo en las células aisladas con anterioridad a su utilización en el constructo sin que existan datos fidedignos sobre las variaciones en el grado de viabilidad que pueden sufrir las células en seno del constructo.…”
Section: Discussionunclassified